Spectators longing for live action: a study of the impact of the COVID-19 pandemic on (football) supporters in Sweden - Radmann, A.; Karlén, S. (Sport in Society: Cultures, Commerce, Media, Politics, 2022)
The purpose of the study is to investigate how sports audiences have been affected by being unable to attend competitions physically on site during the Covid-19 pandemic. The study shows how Swedish supporters, mainly football fans, have experienced the 2020 season, coinciding with the Covid-19 pandemic. The analysis highlights the importance of physical place for the audience and discusses the relationship between physical sports arenas and digital platforms during the pandemic. Finally, the effects of the suspension of live experiences are discussed. According to the persons studied, something essential—fellowship, solidarity, pulse, excitement—is lost when sporting events are held without an audience. The theoretical framework is derived from cultural sociology and draws inspiration from key concepts such as topophilia, space and place, and emotional attachments.